A theoretical and practical picture of Christian vegetarianism in China: Visits and Observations Based on the Seventh-day Adventist Church in Sha County and Xiamen - GAO, Jing (Journal of Research for Christianity in China (JRCC), 2023)
This research report shows the cases of the Seventh-day Adventist Church in Sha County and Xiamen, Fujian Province, China, which adhere to and advocate the vegetarian tradition. This paper introduces the ideological source of Christian vegetarianism advocated bySeventh-day Adventist Church and the important viewpoints of Ellen white，focuses on observing how they understand and practice vegetarianism in Sha county and Xiamen.The team in Sha County, based on the advantages of Sha county snacks famous nationwide, developed and promoted Sha county vegetarian snacks. The team in Xiamen is based on the vacation environment on Kulangyu Island to develop a sanatorium. The case interviews recorded the experiences and feelings of those who accepted the Christian vegetarianism life philosophy，They believe that Christian vegetarianism have indeed brought benefits to their health, which shows that vegetarianism therapy is more attractive to people with health problems. Of course, these cases are not comprehensive, but only provide a perspective for reference.